First Reprocessing of Southern Hemisphere ADditional OZonesondes Profile Records: 3. Uncertainty in Ozone Profile and Total Column. Issue 6 (25th March 2018) - Witte, Jacquelyn C.; Thompson, Anne M.; Smit, Herman G. J.; Vömel, Holger; Posny, Françoise; Stübi, Rene
Abstract: Reprocessed ozonesonde data from eight SHADOZ (Southern Hemisphere ADditional OZonesondes) sites have been used to derive the first analysis of uncertainty estimates for both profile and total column ozone (TCO). The ozone uncertainty is a composite of the uncertainties of the individual terms in the ozone partial pressure ( P O3 ) equation, those being the ozone sensor current, background current, internal pump temperature, pump efficiency factors, conversion efficiency, and flow rate. Overall, P O3 uncertainties (Δ P O3 ) are within 15% and peak around the tropopause (15 ± 3 km) where ozone is a minimum and Δ P O3 approaches the measured signal. The uncertainty in the background and sensor currents dominates the overall Δ P O3 in the troposphere including the tropopause region, while the uncertainties in the conversion efficiency and flow rate dominate in the stratosphere. Seasonally, Δ P O3 is generally a maximum in the March–May, with the exception of SHADOZ sites in Asia, for which the highest Δ P O3 occurs in September–February. As a first approach, we calculate sonde TCO uncertainty (ΔTCO) by integrating the profile ΔPO3 and adding the ozone residual uncertainty, derived from the McPeters and Labow (2012, doi:10.1029/2011JD017006) 1 σ ozone mixing ratios. Overall, ΔTCO are within ±15 Dobson units (DU), representing 5–6% of the TCO. Total Ozone Mapping Spectrometer and Ozone Monitoring Instrument (TOMS and OMI) satellite overpasses are generally within the sonde ΔTCO. However, there is a discontinuity between TOMS v8.6 (1998 to September 2004) and OMI (October 2004–2016) TCO on the order of 10 DU that accounts for the significant 16 DU overall difference observed between sonde and TOMS. By comparison, the sonde‐OMI absolute difference for the eight stations is only 4 DU. Plain Language Summary: Electrochemical concentration cell ozonesondes are balloon‐borne instruments that measure profiles of ozone from launch up to 35 km. The high vertical resolution allows researchers to capture features in measurement‐deficient regions of the atmosphere: the boundary layer, tropopause region that marks the boundary between the troposphere and stratosphere, and the protective ozone shield layer around 20–25 km. The Southern Hemisphere ADditional OZonesondes (SHADOZ) project has been archiving ozonesonde data from up to 17 stations since 1998 that are available publicly at https://tropo.gsfc.nasa.gov/shadoz . As with any instrument there are uncertainties in the measurements. For ozonesondes the uncertainty in the ozone measurement is associated with the mechanics of the electrochemical concentration cell sensor and the preparation procedures. For the first time we calculate the ozone profile uncertainties measured by the ozonesonde using the SHADOZ 1998–2016 database. The advantage of doing a detailed uncertainty analysis is that it reveals areas of the measurements where we can refine operational procedures to reduce the uncertainty and where additional research is needed to improve the basics of this measurement. Key Points: First estimates of ECC ozonesonde uncertainties using SHADOZ data records Ozone uncertainties are generally within 15% and peak around the tropopause where ozone measurements approach the uncertainty estimates Uncertainties in background and sensor current dominate the troposphere, while conversion efficiency and flow rate dominate the stratosphere